Deixis Analysis in Hi, Mom: Ni hao Hao Li Huanying《你好，李焕英》Film - Niza Ayuningtias; Laura Mutiara Lumban Gaol (PT FORMOSA CENDEKIA GLOBAL, 2023)
Pragmatic theory by Levinson is the theory used by the author in this research. Descriptive analysis is a research method used by the author. In the research, the data found came from sentences, dialogues and words or text contained in the film Hi, Mom 《你好，李焕英》. In this study, the results obtained show that there are five types of deixis in Mandarin in the film Hi,Mom 《你好，李焕英》 namely: persona deixis, place deixis, time deixis, discourse deixis, and social deixis. Based on the results of the analysis of the use of deixis in the film Hi, Mom《你好，李焕英》 the authors conclude that deixis in this study uses gestural use, namely the way of conveying speech/speech of appointment together with the use of body movements. Meanwhile, the use of deixis symbolically means that the way in which speech is conveyed is not accompanied by bodily movements.